Diverging paths: Labor reallocation, sorting, and wage inequality - Erwin Winkler (ZBW - Leibniz Information Centre for Economics, 2020)
This paper provides evidence that labor reallocation from the manufacturing into the non-manufacturing sector causes an increase in sorting of high-skilled (low-skilled) workers into high-paying (low-paying) firms and thereby triggers a rise in wage inequality. I use data on 50% of all West German male employees and exploit industry-level variation in trade-induced labor reallocation into the non-manufacturing sector, stemming from Germany's trade integration with China and Eastern Europe. The results suggest that labor reallocation into the non-manufacturing sector causes an increase in sorting because low-educated workers performing routine and codifiable tasks are less likely to move to high paying service firms than more skilled workers. These results are not specific to trade-induced labor reallocation, but carry over to any shock or policy which causes a contraction of the manufacturing sector and labor reallocation into the service sector. A back-of-the-envelope calculation suggests that total observed labor reallocation into the non-manufacturing sector explains at least 30% of the rise in sorting and 10% of the rise in wage inequality between 1990 and 2010 in Germany.
Keywords: J31; J62; F14; 330; Labor reallocation; wage inequality; sorting; firms; international trade